Mechanochemical conversion of domestic celestite mineral to SrC2O4 in the ammonium oxalate media - Mert Zorağa (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The mainraw material used in the production of Sr metal and its compounds is SrSO4(celestite) mineral and Turkey has valuable Sr mineral deposits. One of theimportant steps in the production of Sr compounds is the production ofstrontium oxalate compound that does not contain alkali compunds ascontamination. Strontium is used as a primary raw material in the production ofoxalate, superconducting material and luminescence. In thisstudy, the in situ conversion of SrSO4 into SrC2O4.H2Oby ammonium oxalate is investigated and the effect of rotation speed, ball /sample ratio and solution concentration on the conversion reaction has beendetermined. It was found that the conversion of SrO4 to SrC2O4.H2Owas increased with the increase in mole ratio of (NH4)2C2O4to SrSO4. The maximum conversion, above 70 %, was achieved by using(NH4)2C2O4 / SrSO4 moleratio: 1.5, rotation speed: 500 rpm and ball / sample ratio: 13.